Perfusion Strategy for Minimally Invasive Cardiac Surgery - Oleksandr D. Babliak; Volodymyr M. Demianenko; Anton I. Marchenko; Lilia V. Pidgaina; Dmytro Ye. Babliak; Oleksii S. Stohov (Ukrainian Journal of Cardiovascular Surgery, 2021)
Minimally invasive cardiac surgery (MICS) has a number of proven advantages compared to median sternotomy. Safe cannulation and perfusion are some of the main components of the success of MICS.The aim. To present our perfusion strategy and describe the methods of cannulation, technical features, contraindications and potential complications.Materials and methods. We examined the results of 1088 adult patients who underwent primary cardiac surgery in our hospital (coronary artery bypass grafting, valve surgery, aortic surgery, left ventricle repair, congenital cardiac surgery and combined procedures) from July 2017 to May 2021. Of these, 851 patients were qualified for MICS. To select a safe cannulation strategy, we performed contrast enhanced computed tomography (CT) of the aorta and main branches for all the patients, also we calculated the body surface area according to the DuBois and DuBois formula.Results. We performed 838 minimally invasive on-pump procedures, which is 98.5% of all patients qualified for MICS. According to the results of the preoperative CT scan, 13 (1.5%) patients were not operated with the minimally invasive approach due to the hazards related to the provision of cardiopulmonary bypass. Peripheral cannulation was performed in 754 (90%) patients and an alternative cannulation site was selected in 62 (8.2%) patients based on preoperative CT data. There were 10 (1.32%) patients who developed major complications (stroke, acute aortic dissection, acute renal failure requiring hemodialysis) after peripheral cannulation.Conclusions. Preoperative CT scan is mandatory for planning a perfusion strategy in minimally invasive cardiac surgery. The required surgical techniques should include cannulation of the right and left femoral and right axillary arteries.